Bob Dexter and the Storm Mountain Mystery; or, The Secret of the Log Cabin - Baker, Willard F. (Salt Lake City, UT : Project Gutenberg, 2015)
"Bob Dexter and the Storm Mountain Mystery; or, The Secret of the Log Cabin" by Willard F. Baker is a detective novel written in the early 20th century. The story follows the adventures of Bob Dexter, a young and aspiring detective, as he navigates the challenges of solving a mystery surrounding an old man named Hiram Beegle, who has been assaulted and robbed. The narrative is filled with intrigue as Bob strives to uncover the truth behind the robbery while dealing with the complications of his responsibilities to his uncle. At the start of the story, Bob Dexter is approached by his friends who are eager to attend a baseball game, but Bob must fulfill a duty for his uncle by waiting for important papers from a businessman. After successfully retrieving the papers, he encounters Hiram Beegle, who has been knocked unconscious and robbed in his secluded log cabin. As Bob takes charge of the situation, he learns about the brass-bound box Hiram was protecting, leading to a deeper investigation that reveals a web of deception connected to a figure named Rod Marbury. The opening establishes a rich setting for mystery, highlighting Bob's determination and curiosity as he seeks to unravel the circumstances of the robbery while becoming embroiled in the complexities of friendship, duty, and the pursuit of justice. (This is an automatically generated summary.)
Release date is 2015-01-31
Produced by Roger Frank
Keywords: Detective and mystery stories; Boys -- Juvenile fiction